Hubungan tingkat aktivitas fisik dan indeks massa tubuh terhadap agility pada mahasiswa FK UNS - Pramudita, Andika Putra; Hastami, Yunia; Ghozali, Dhoni Akbar; Munawaroh, Siti (Jurnal Sport Science, 2023)
Technology and life today have a big influence, especially on the phenomenon of people’s physical activity and body mass index, plus medical students who have a heavy study load will certainly have an influence on these two things. Low physical activity and uncontrolled body mass index will have a major impact on a person's physical fitness, one of the its components is agility. This study aims to determine the relationship between physical activity level and body mass index on agility. This research is a quantitative research with an observational study with a cross sectional approach on 35 students majoring in medicine at Sebelas Maret University who were selected using random sampling techniques. Physical activity was tested using the Indonesian version of the IPAQ SF questionnaire, BMI was tested by measuring the students' height and weight and agility was tested using the Illinois Agility Run Test. The results showed that most of the medical students fell into the moderate category of physical activity level (18 people) and normal body mass index (16 people) but were not too far from those included in the obese category (15 people), none of the students' agility fell into the category good & excellent and most of them fall into the below average (13 people) and poor (12 people) categories. The results obtained were then calculated using Spearmann correlation analysis showing that the physical activity and agility variables had a significance value of p=0.000 with a correlation coefficient of 0.646. The variables body mass index and agility have a significance value of p=0.227 with a correlation coefficient of 0.210. The relationship between the physical activity variable and agility is significant with a strong correlation, while the body mass index variable and agility has an insignificant relationship